Assessing the Magnitude of Risk for ADHD in Offspring of Parents with ADHD: A Systematic Literature Review and Meta-Analysis. Issue 13 (November 2021) - Uchida, Mai; Driscoll, Haley; DiSalvo, Maura; Rajalakshmim, Aarya; Maiello, Marco; Spera, Vincenza; Biederman, Joseph
The main aim of this study was to examine the body of knowledge on the prevalence of Attention Deficit Hyperactivity Disorder (ADHD) in "high-risk" children whose parents are diagnosed with ADHD. This knowledge could aid early identification for children presenting with ADHD symptoms at a young age. We conducted a systematic search of the literature assessing high-risk children. Included were original articles published in English with the main aim to assess prevalence of ADHD in high risk children. In addition, a meta-analysis was conducted to examine this prevalence. Four articles met our inclusion and exclusion criteria all suggesting an increased prevalence of ADHD in children of parents with ADHD. The meta-analysis also confirmed the increased prevalence of ADHD in high-risk children. The literature indicates that children of ADHD parents have an increased risk of developing ADHD compared to control children.